Prediksi Emisi Karbondioksida Dari Kegiatan Transportasi Di Kecamatan Tampan - Febrian Maulana; Aryo Sasmita; Shinta Elystia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The growth of economic and population, especially in tampan district Pekanbaru is followed by the increase of transportation infrastructures and increasing amount of vehicle result in the increasing amount of vehicle. This increasing amount of vehicles result in the increasing amount of carbondioxide (CO2) emission produced. CO2 will enlarge the Greenhouse Effect which can cause global warming. Because of that, a measurement is needed to find out the amount of CO2 emission produced transportations activities. In this research, the measurement is done by total vehicle appoarch and emission factor. This research was conducted Soebrantas Street, Lobak, Bangau Sakti, Kamboja, Purwodadi and Suka Karya. The total amount of vehicles is measured with video recorder on at research locations for 16 hours. The recording was conducted on effective days. From the measurment, CO2 emission from transportations activities for converted vehicles in Tampan district is 169.786,914 kg CO2 on effective days.Keywords : carbondioxide emission, carbon footprint, global warming, emission factor, transportation